Creating a Sustainable Future (Journal of Universal Excellence, 2026)
Research Question: In the research, with the help of selected articles, we asked a research question, how to create and upgrade a sustainable future in organisationPurpose: Teoretical presentation of the EFQM Bussines Excellence Model and self-assessment emphasis on Creating sustainable future of importance for leaders of organisations and presentation of environmental, social and economic effects.Method: In the research, we used a qualitative method based on analythical study. We collected litherature, articles, and information and reviewed and analyzed them.Results: The research found that creating a sustainable future requires an equal emphasis on the social, enviroment and economy, and the key is the support of top management, which leads to the business excellence of the organization.Organization: Research and study of various articles gives us information about the inportance of leaders in the organization and strategic orientation towards a sustainable future.Society: The organization is the one that can do the most for the social environment and its competitive and economic advantage through its activities for a sustainable future.Originality: The research includes three factors that, with the help of leaders and stakeholders, lead to a sustainable future.Limitations/Future Research: The research was conducted on the basis of collected literature, articles and information.
Keywords: organization; leaders; sustainable future; environmental effects; social effects